Espectroscopia Raman e histopatologia clássica na avaliação de tendinite induzida por colagenase em ratos wistar - Silva, Eveline Junqueira (2005)
In this work, a new approach, still little explored, was used for the evaluation and quantification of tendonitis through Raman spectroscopy, with low resolution spectrometers (785 nm), and chemometric methods. For this, the experimental model of tendonitis produced by intratendinous collagenase in Rattus norvegicus variety Wistar was used. In addition to spectroscopic methods, the evaluation of the intratendinous inflammatory process was carried out through a classical histopathological study using microscopic evaluation of tissues stained with hematoxylin-eosin (HE). It was proposed to use mathematical methods for the pre-processing of the spectra (removal of matrix effects from the tissues and identification of bands) and the use of chemometric methods for the efficient modeling of the method developed, due to the low resolution of the spectrometer and structural similarity of the evaluated tissue, which leads to strong spectral similarity. The analysis of the results showed us that it is possible to evaluate the evolution of the tendonitis process through Raman spectroscopy whose results were strongly correlated with the findings.